CAMEL As A Mathod Used For Assessing The Performance - Gede Putu Agus Jana Susila (AFEBI Management and Business Review, 2017)
As the role played by the Village Credit Union hereinafter referred to as Lembaga Perkreditan Desa (LPD) in the economic development of the rural society is important, the result of its performance in the form of the adequate financial statement should be presented to make people trust its existence. This present study is intended to identify how healthy the LPD Units in Gerokgak District, Buleleng Regency are using the CAMEL method for the period 2015-2016. The aspects used to assess how healthy the LPD is are as follows: (1) Capital with one ratio, namely CAR, (2) Assets with two ratios, KAP and CPRR, (3) Management, (4) Earnings with two ratios, namely ROA and BOPO, and (5) Liquidity with two ratios, namely liquid instrument and LDR. The LPD could fulfill the criterion of being healthy as the average CAMEL credit value achieved was higher than 81 (the minimum limit of being healthy). Based on the analysis of how healthy the LPD from 2015 to 2016 were, it can be concluded that: (1) The CAMEL credit value achieved in 2015 was 86.48 points. (2) In 2016, the fact that the CAMEL credit value achieved in 2016 was 88.72 points.Keywords: CAMEL, Village Credit Union (LPD)